2015
DOI: 10.1007/s11357-015-9820-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between cognition and gene polymorphisms involved in thrombosis and haemostasis

Abstract: An association between blood markers of thrombosis and haemostasis and cognitive decline has been described. These results may be confounded by lifestyle and environmental factors. We used a Mendelian randomisation approach to describe the association between thrombosis/haemostasis genotypes and cognition. We studied the genetic variants (single nucleotide polymorphisms) of circulating markers of thrombosis and haemostasis. Our chosen blood factors and associated polymorphisms were D-dimer [rs12029080], fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Two studies [ 8, 9 ] examined fibrinogen in relationship to global cognition with neither study finding genetic evidence for a causal relationship. In addition to fibrinogen, Quinn and colleagues [ 9 ] also investigated D-dimer, plasminogen activator inhibitor and von Willebrand factor but found no evidence for an association between any of the IVs for these measures and global cognition ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies [ 8, 9 ] examined fibrinogen in relationship to global cognition with neither study finding genetic evidence for a causal relationship. In addition to fibrinogen, Quinn and colleagues [ 9 ] also investigated D-dimer, plasminogen activator inhibitor and von Willebrand factor but found no evidence for an association between any of the IVs for these measures and global cognition ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…If results from multiple cohorts were combined, we extracted only pooled findings. We also tried to contact corresponding authors of studies where relevant data was not fully reported [ 7–9 ] and received additional data for one study [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30]. Эти изменения системы гемостаза увеличивают не только риск сердечно-сосудистых событий, но и приводят к когнитивным расстройствам [31]. Также сообщалось, что у пожилых людей отмечается повышение уровня различных маркеров воспаления, таких как С-реактивный белок и интерлейкин-6 [32].…”
Section: ишемический и геморрагический риск у пациентов пожилого и ст...unclassified